Safety evaluation and whole genome sequencing for revealing the ability of Penicillium oxalicum WX-209 to safely and effectively degrade citrus segments - Xiao Hu; Yujiao Qian; Zhipeng Gao; Gaoyang Li; Fuhua Fu; Jiajing Guo; Yang Shan (Food Science and Human Wellness)
The microbial potential of Penicillium has received critical attention. The present research aimed to elucidate the efficacy of crude enzyme secreted from Penicillium oxalicum WX-209 in degrading citrus segments and evaluate the safety of the process. Results showed that citrus segment membranes gradually dissolved after treatment with the crude enzyme solution, indicating good degradation capability. No significant differences in body weight, food ingestion rate, hematology, blood biochemistry, and weight changes of different organs were found between the enzyme intake and control groups. Serial experiments showed that the crude enzyme had high biological safety. Moreover, the whole genome of P. oxalicum WX-209 was sequenced by PacBio and Illumina platforms. Twenty-five scaffolds were assembled to generate 36 Mbp size of genome sequence comprising 11 369 predicted genes modeled with a GC content of 48.33 %. A total of 592 genes were annotated to encode enzymes related to carbohydrates, and some degradation enzyme genes were identified in strain P. oxalicum WX-209. Data availability: The whole genome sequencing data in this study can be found in GenBank database of NCBI website with the accession number PRJNA 715321. The link: http://www.ncbi.nlm.nih.gov/bioproject/715321.